Pengaruh Stimulasi Oral terhadap Peningkatan Refleks Hisap Lemah pada Bayi Premature - Putri, Anggi Resina; Sukmakarti, Laksmy Dewi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Preterm infants often experience weak sucking reflexes due to the immaturity of the oromotor neuromuscular system. This condition leads to delays in the development of oral feeding skills, increases the risk of aspiration, and prolongs hospitalization in the NICU. Oral stimulation is a non-invasive intervention aimed at facilitating the maturation of sucking–swallowing abilities in preterm infants. Recent studies have demonstrated the effectiveness of this intervention; however, a comprehensive summary of research findings is needed to strengthen clinical recommendations. Objectives: To determine the effect of oral stimulation on improving weak sucking reflexes in preterm infants. Methods: This study employed a systematic review design using a literature review approach that included five published studies from the past five years. Results: All five studies indicated that weak sucking reflexes in preterm infants are primarily caused by neuromuscular immaturity and poor suck–swallow–breathe coordination. Oral stimulation interventions—such as PIOMI, oral motor stimulation, and non-nutritive sucking—were shown to significantly improve sucking strength, sucking frequency, physiological stability, and the ability to transition to oral feeding. All studies reported accelerated achievement of full oral feeding, and most demonstrated a reduction in NICU length of stay. Conclusion: Oral stimulation has been consistently proven effective in improving the sucking reflex of preterm infants and accelerating readiness for oral feeding. This intervention is safe, easy to administer, and recommended as part of routine NICU care to support feeding maturation and enhance clinical outcomes. Keywords: Oral stimulation, Sucking reflex, Preterm infants, Oral feeding ability